Why Do Some Countries Spend More for Health? An Assessment of Sociopolitical Determinants and International Aid for Government Health Expenditures - Liang, Li-Lin; Mirelman, Andrew J. (World Bank, Washington, DC, 2014)
A consensus exists that rising income levels and technological development are among the key drivers of total health spending. However, determinants of public sector health expenditure are less well understood. This study examines a complex relationship across government health expenditure (GHE), sociopolitical risks, and international aid, while taking into account the impact of national income and fiscal capacity on health spending. The author apply a two-way fixed effects and two-stage least squares regression method to a panel dataset comprising 120 countries for the years 1995 through 2010. Our results show that democratic accountability has a diminishing positive correlation with GHE, and that levels of spending are higher when the government is more stable. Corruption is associated with less spending in developing countries, but with more spending in high-income countries. Furthermore, the author find that development assistance for health (DAH) substitutes for domestically financed government health expenditure (DGHE). For an average country, a 1 percent increase in total DAH or DAH to government is associated with a 0.02 percent decrease in DGHE. Our work highlights that policy reforms that aim to eliminate corruption are fundamental to improving the capacity of developing countries to scale up GHE, and to increasing the efficiency of health care systems in developed countries in containing health care costs. To minimize fungibility, donors may impose stronger monitoring mechanisms for corruption. Delivering aid through NGOs may be an option in countries with high ethnic tensions; however, the ability to do so depends on institutional arrangements and the capacity of NGOs in individual countries.